Determination of the Estimated Amounts of Discarded Face Masks due to COVID 19 in Turkey - Topal, Murat; Topal, Emine Isil Arslan (Univ Tehran, 2021)
In this study, the estimated amounts of discarded face masks due to COVID 19 were investigated. In this context, the amount of waste face masks was determined separately according to the mask types used (nonwoven, meltblown, and 3-ply, pleated) and the importance of waste face masks was revealed. According to obtained data, the estimated total daily face mask use in Turkey is 72,351,638. The highest amounts of nonwoven, meltblown, and 3-ply face mask waste were determined as 26.88, 36.29, and 43.68 tonnes/day for Istanbul city, respectively. Total amounts of nonwoven, meltblown and 3-ply face mask waste in Turkey were calculated as 144.7, 195.35, and 235.14 tonnes/day, respectively. The top 5 provinces with the highest amount of waste masks are listed as follows; Istanbul (nonwoven=26 .88, meltblown=36 .29, 3ply=43 .68 tonnes/day), Ankara (nonwoven=9 .91, meltblown=13 .38, 3ply=16.11 tonnes/day), Izmir (nonwoven=7.76, me ltblown=10.47, 3ply=12 .61 tonnes/day), Bursa (nonwoven=5.40, meltblown=7.29, 3ply=8.78 tonnes/day), and Antalya (nonwoven=4.45, meltblown=6.01, 3ply=7.23 tonnes/day), respectively. In Turkey, 91.3% of medical waste collected in health institutions in 2019 (90,920 tonnes) was sterilized and disposed of in storage areas (83,010 tonnes). 8.7% of medical waste was sent to incineration facilities and disposed (7,910 tonnes). Considering these values, 132, 178.35, and 214.7 tonnes/day of nonwoven, meltblown, and 3-ply face mask wastes can be disposed by sterilization and the remaining 12.7, 17, and 20.44 tonnes/day by incineration, respectively.
Keywords: Health; pandemic; pollution; SARS-CoV-2; waste